(untitled) (Foro de Educacion, 2017)
In a social and economic framework increasingly composite and articulated, the internationalization of education and student mobility represent an attempt by educational institutions to meet the demands and challenges of globalization because they offer the means of personal development of students, enrich the human capital, increasing the employability through the acquisition and exchange of knowledge, increase the development of language and intercultural skills, promote contacts. The internationalization of education and student mobility are two key priorities for the European Union, for the contribution they can make not only to the growth of economies and societies, because they increase the social progress, cultural and economic, promoting active citizenship and ethical values, but also for the modernization of universities, in order to make them more competitive in the European territory in a global knowledge economy.